Pengenalan Kosakata Bahasa Inggris Sederhana melalui Nursery Rhymes bagi Siswa TK A - Setianingsih, Ika Sulis; Dewi Kodrat Ningsih, Ida Nuraini (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
The golden age makes early childhood students quickly learn something, both in everyday terms and in language learning, including learning foreign languages. This is what makes nursery rhymes become one of the options for learning foreign languages for early childhood. This activity aims to provide an initial introduction to simple English vocabulary through movements and songs using nursery rhymes. This activity is a series of activities carried out during Parents Week where parents play the role of teachers on special days. This community service activity is carried out in several stages, namely preparation, discussion, and core activities. Kindergarten students were enthusiastic and happy during the activity. Through this activity, it can be concluded that nursery rhymes have proven to be effective for use in learning in Kindergarten A, in accordance with the results of previous research.